Cavum septum pellucidum: Significance and management - Santanu Bora; Amit Purushottam Tirpude; Manisha Gaikwad; Rabi N Sahu; Lalsangzuala Chinzah; Babita Kujur; Arpan Haldar (Wolters Kluwer Medknow Publications, 2019)
Cavum septum pellucidum (CSP) is a cystic midline brain malformation; it is mostly congenital but can also be acquired. CSP is mostly asymptomatic. Symptomatic CSP is very rare. Clinical presentation is usually nonspecific which may be due to increased intracranial pressure as a result of obstructive hydrocephalus or due to direct compression of the nearby structures. Diagnosis of CSP is not very easy specially relating its contribution to the presenting symptoms is difficult. However, once diagnosis is established surgery remains the treatment of choice. Nowadays endoscopic fenestration of the cyst is the surgical modality of choice. The outcome after surgical intervention is very promising with relief of obstructive symptoms along with improvement of cognitive function and behavioral symptoms.